Detection of Interturn Short-Circuit Faults in Dry-Type Voltage Transformers Using the Pulse Voltage Method - Hongyan Nie; Hongxin Wang; Wei Wang; Yuanhang Yao (Energies, 2023)
This article investigates the application of the pulse voltage method for detecting interturn short-circuit faults in the high-voltage windings of dry-type voltage transformers. We determined the characterization parameters of the high-voltage windings of dry-type voltage transformers and trends in the variation of the characterization parameters with frequency in the presence and absence of faults. The viability of using the pulse voltage method for the detection of interturn short-circuit faults in dry-type voltage transformers was analyzed. A pulse voltage test platform was designed to analyze the response voltage waveforms using pulse-oscillating voltage experiments on transformers with various short-circuit faults. The results demonstrate that during a turn-to-turn short circuit, the equivalent resistance and inductance of a high-voltage winding are significantly lowered. When employing the pulse voltage method to investigate interturn short-circuit faults, tiny inductors are connected in parallel to produce an oscillating voltage waveform that is more uniform. Upon incurring a short circuit between turns, the pulse’s oscillating voltage frequency increases. The greater the number of turns in the short-circuit fault is, the more significant the effect of the test.